2022
DOI: 10.12775/jehs.2022.12.01.032
|View full text |Cite
|
Sign up to set email alerts
|

General non-specific effects of balneofactors of Truskavets’ spa on parameters of neuroendocrine regulation, metabolism, immunity and microbiota in patients with chronic pyelonephritis and cholecystitis

Abstract: Background. Earlier in experiments on rats, it was shown that drinking mineral water, regardless of their mineralization and chemical composition, have similar (nonspecific) course effects on a number of parameters of metabolism and neuroendocrine-immune complex. The aim of this study is to identify such parameters in patients of Truskavets’ spa who received complex drinking balneotherapy. Materials and Methods. The object of clinical-physiological observation were 34 men aged 23-70 years, who underwent rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(16 citation statements)
references
References 5 publications
1
15
0
Order By: Relevance
“…Overactivation 0,26 Strain Index-1 = [(Eo/3,5-1) 2 + (SN/3,5-1) 2 + (Mon/5,5-1) 2 + (Leu/6-1) 2 ]/4. Parameters of phagocytic function of neutrophils estimated as described by Kovbasnyuk MM [33,49]. The objects of phagocytosis served daily cultures of Staphylococcus aureus (ATCC N 25423 F49) as typical specimen for Gram-positive Bacteria and Escherichia coli (O55 K59) as typical representative of Gram-negative Bacteria.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Overactivation 0,26 Strain Index-1 = [(Eo/3,5-1) 2 + (SN/3,5-1) 2 + (Mon/5,5-1) 2 + (Leu/6-1) 2 ]/4. Parameters of phagocytic function of neutrophils estimated as described by Kovbasnyuk MM [33,49]. The objects of phagocytosis served daily cultures of Staphylococcus aureus (ATCC N 25423 F49) as typical specimen for Gram-positive Bacteria and Escherichia coli (O55 K59) as typical representative of Gram-negative Bacteria.…”
Section: Materials and Research Methodsmentioning
confidence: 99%
“…The described changes in parameters of EEG, HRV, hormones and bioelectrophotonics are negatively/positively correlated with the changes in parameters of phagocytosis [21,31,33,47,49] (as well as of immunity [21,31,34,35,[46][47][48]), so effects of the treatment are physiologically favorable and therefore adaptogenic.…”
Section: Root/variabl Correlationmentioning
confidence: 99%
See 1 more Smart Citation
“…Unified methods are applied. Urinary syndrome was assessed by quantitative and qualitative levels of bacteriuria and leukocyturia [7,20]. The inclusion criteria were the presence of pronounced urinary syndrome (bacteriuria: 0,285÷0,715 points; leukocyturia: 0,1÷0,5 points) with preservation of functional renal reserve (>10%), previously assessed by the Gozhenko AI method [6].…”
Section: Methodsmentioning
confidence: 99%
“…However, it is well known that even fresh Naftussya water affects such tests ambiguously [11,22,28], so they do not reflect the inherent properties of Naftussya water, that is, they are not attributive. The Truskavetsian Scientific School has shown that the most characteristic manifestation of the biological activity of Naftussya water is the stimulation of phagocytosis in both rats and humans [11,14,[20][21][22]25] caused by its organic substances, in particular, polyphenols [4,10] as Ah receptor ligands [22]. Such an effect of organic substances on phagocytes is realized not directly, but through the mediation of the nervous and endocrine system, the mediators and hormones of which activate phagocytosis [13,14,21,22].…”
Section: Inroductionmentioning
confidence: 99%